2017
DOI: 10.1159/000478645
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-133b Ameliorates Allergic Inflammation and Symptom in Murine Model of Allergic Rhinitis by Targeting Nlrp3

et al.

Abstract: Background: Emerging evidences indicate that post-transcriptional regulation by microRNAs is critical in allergic rhinitis (AR) pathogenesis. MircroRNA-133b (miR-133b) was recently suggested as a potential predictor of AR. However, the in vivo effect of miR-133b on AR is unclear. Methods: AR model was established in BALB/c mice by intraperitoneal sensitization and intranasal challenge with ovalbumin (OVA). MiR-133b agomir was then intranasally administrated to mice after OVA challenge for another 7 days. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 31 publications
1
52
1
Order By: Relevance
“…Studies with HEK293T cells transfected with miR‐133b and a luciferase reporter conjugated to 3′UTR of murine Nlrp3 mRNA suggested that miR‐133b binds to the 3′UTR of murine Nlrp3 mRNA to negatively regulate Nlrp3 mRNA expression . Overexpression of miR‐133b in HEK293T cells reduced the protein levels of NLRP3, whereas inhibition of miR‐133b increased the protein levels of HEK293T cells in vitro . Importantly, miR‐133b inhibited NLRP3 inflammasome activation and ameliorated allergic inflammation in a mouse model of allergic rhinitis .…”
Section: Negative Regulation Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with HEK293T cells transfected with miR‐133b and a luciferase reporter conjugated to 3′UTR of murine Nlrp3 mRNA suggested that miR‐133b binds to the 3′UTR of murine Nlrp3 mRNA to negatively regulate Nlrp3 mRNA expression . Overexpression of miR‐133b in HEK293T cells reduced the protein levels of NLRP3, whereas inhibition of miR‐133b increased the protein levels of HEK293T cells in vitro . Importantly, miR‐133b inhibited NLRP3 inflammasome activation and ameliorated allergic inflammation in a mouse model of allergic rhinitis .…”
Section: Negative Regulation Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…Several other miRs have also been implicated in regulating Nlrp3 mRNA expression in various inflammatory settings. Studies with HEK293T cells transfected with miR‐133b and a luciferase reporter conjugated to 3′UTR of murine Nlrp3 mRNA suggested that miR‐133b binds to the 3′UTR of murine Nlrp3 mRNA to negatively regulate Nlrp3 mRNA expression . Overexpression of miR‐133b in HEK293T cells reduced the protein levels of NLRP3, whereas inhibition of miR‐133b increased the protein levels of HEK293T cells in vitro .…”
Section: Negative Regulation Of Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…Several lines of evidence indicate that miR-133b is relevant to the inflammatory response and lung remodeling in allergic asthma. Lower levels of circulating miR-133b have been detected in asthmatic patients [22], and its overexpression in nasal mucosa was shown to target the Nlrp3 inflammasome and reduce eosinophil infiltration and IgE, TNF-α, IL-4, IL-5 and IFN-γ levels in mice sensitized/challenged with OVA [23].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showing that miR-133b is more than only a biomarker for allergic asthma came from studies with mice demonstrating that the model of sensitization and challenge with OVA leads to a reduction in miR-133b expression in nasal mucosa. It was further demonstrated that upregulation of miR-133b with an specific agomir was able to abrogate OVA-induced increased in IgE, IL-4, IL-5 and TNF-α levels and lung eosinophil infiltration [23].…”
Section: Mice Born To Hfd-fed Mice Have Increased Mirnas That Are Assmentioning
confidence: 96%
“…Recent studies have identified that NLRP3 can be regulated by several miRNAs including miR-223 (Xie et al, 2017), miR-133b (Xiao, Jiang, Hu, & Li, 2017), miR-495 (T. Zhou et al, 2018), and miR-22 (Huang, Wei, Lin, & Huang, 2017) in various diseases. Of note, the expression pattern of miRNAs is also tissue-specific, which keeps line with the tissue-specific pathological process.…”
mentioning
confidence: 99%